It’s awe-fully unfamiliar: The effect of familiarity on awe within a virtual reality setting - Ochadleus, Cassidy; Kirby, Charissa; Scollon, Christie Napa (Frontiers in Psychology, 2023)
Awe-inducing scenes are purported to involve vastness and a need for accommodation. Familiarity with a stimulus should reduce the need for accommodation, thereby reducing the intensity of awe experienced. The present study tested the effect of familiarity to a natural awe-inducing scene on the experience of awe. Forty undergraduate participants (N = 40) participated in a virtual reality experiment. Using a within-subjects design, participants viewed (in counterbalanced order) an awe-inducing nature scene that was either familiar or unfamiliar. The dependent measure was self-reported awe. Results confirmed that participants experienced diminished awe while viewing a familiar awe-inducing scene compared to viewing an unfamiliar awe-inducing scene.